2016
DOI: 10.1021/acs.chemmater.6b01681
|View full text |Cite
|
Sign up to set email alerts
|

A Room-Temperature, Solution Phase Method for the Synthesis of Mesoporous Metal Chalcogenide Nanocrystal-Based Thin Films with Precisely Controlled Grain Sizes

Abstract: Block copolymer templating of ligand-stripped nanocrystals followed by thermal degradation of the polymer template is a robust method that has been applied in making a variety of mesoporous nanocrystal-based films. However, the use of thermal processing to remove the polymer template can have detrimental effects on other material properties such as grain size and crystal structure that affect size-dependent properties such as the band gap.Here we present a new method for forming mesoporous films of cadmium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 90 publications
2
14
0
Order By: Relevance
“…The general SEM and SAXS characteristics were largely similar to the in situ series, albeit with a lesser degree of ordering apparent by SEM ( Figures and and Figure S9, Supporting Information). This is consistent with recent examples of micelle assembly with preformed nanoparticles that generally result in rougher interfaces and a lesser degree of symmetry due to retention of the starting nanoparticle shape . The trends in SAXS d‐spacing were analyzed using the described log–log coordinate space (Figure a).…”
Section: Resultssupporting
confidence: 82%
“…The general SEM and SAXS characteristics were largely similar to the in situ series, albeit with a lesser degree of ordering apparent by SEM ( Figures and and Figure S9, Supporting Information). This is consistent with recent examples of micelle assembly with preformed nanoparticles that generally result in rougher interfaces and a lesser degree of symmetry due to retention of the starting nanoparticle shape . The trends in SAXS d‐spacing were analyzed using the described log–log coordinate space (Figure a).…”
Section: Resultssupporting
confidence: 82%
“…Simply by changing the solvent conditions, block copolymers enable the generation of tunable mesostructures with ultralarge pores. A few studies on mesoporous metal sulfides, such as MoS 2 , CdS, ZnS, and Ag 2 S have been reported by using this soft-template method. But to the best of our knowledge, methods that enable well-defined metal sulfide architectures with uniform and adjustable pore sizes have not been created. Especially, synthesis of mesoporous multimetallic sulfides ( e.g ., NiMoS and CoMoS), which are potential candidates for electrochemical applications, has not been reported.…”
mentioning
confidence: 99%
“…[ 1–7 ] Among the mesoporous materials, highly crystalline mesoporous metal sulfides (MMSs) with ideal band‐edge, unique atomic arrangement, and excellent electronic properties have shown potential applications in sensors, solar cells, and photocatalysis. [ 8–13 ] Hitherto, hard‐templating method is an effective method for the synthesis of MMSs, which mainly relies on the usage of mesoporous silica as a hard template to provide the desired mesoporous structure. [ 14,15 ] The classical route is infiltrating metal sulfides precursors into hard templates and then removing the templates through etching to finally obtain MMSs.…”
Section: Introductionmentioning
confidence: 99%